Effect of mechanical activation on sintering behaviour of tetragonal zirconia nanopowders. Issue 9 (15th June 2020) - Lakusta, Marharyta; Danilenko, Igor; Volkova, Galina; Loladze, Larisa; Golovan, Galina; Brukhanova, Iryna; Glazunova, Vanentina; Popov, Inna; Mazur, Olga; Konstantinova, Tetyana
Abstract: The effect of mechanical activation on the densification behavior of tetragonal zirconia nanopowders has been investigated. The obtained non-isothermal sintering data of nanopowders densification at the initial sintering stage reveal a correlation between the milling duration, mechanical energy and change in the sintering mechanisms. It was found that the effect of mechanical activation on sintering depends on duration of the mechanical process. The mechanical energy accumulated in the nanoparticle system as deformation energy and phase transformation led to nonlinear change in the sintering mechanisms at the initial stage of sintering and increased the activation energy of densification process. It was calculated the critical values for the duration of mechanical activation and the mechanical energy accumulated in nanopowders at which the sintering mechanisms were changed from VD to GBD. Our results enable controlling the influence of mechanical activation on diffusion in 3Y-TZP and predicting final physical and mechanical properties of zirconia ceramics.